DAMPAK PANDEMI COVID-19 TERHADAP ANGKUTAN UMUM - Roni Agusmaniza; Ferdiansyah Novriza (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
AbstractThe most noticeable change during the COVID-19 pandemic was that fewer people travel from one place to another unless it was very urgent. This was mainly driven by the government's instruction not to carry out activities outside the home except for vehicles transporting goods. The government appeal decreases public transportation operations and reduces the income of public transportation service providers. This study aimed to determine and analyze the impact of the COVID-19 pandemic on public transportation (passengers and goods) from Aceh Barat to Medan. The descriptive quantitative method was used in this research. Data collection was carried out through direct surveys and questionnaires, which were randomly distributed to public transport drivers (passengers/goods) at the passenger and freight terminals during working hours. The survey data were analyzed using multiple linear analyses with the help of SPSS software to observe the influence of the independent variable (X) on public transportation (passengers/goods) during the pandemic (Y). The results obtained from the analysis indicated that there are several equations obtained, the equation for passenger transportation: Y1 = 0.298 - 0.770X1 + 0.113X6 and the equation for freight transportation: Y2 = 0.113 + 0.546 X3 + 0.338 X6. From this equation, it can be concluded that there is a relationship between the amount of income (X1), travel time (X3), and expenditure costs (X6) on the impact on public transportation during the COVID-19 pandemic. Keywords— Impact of the COVID-19 Pandemic, Passenger Transport, Goods Transport